Directed synthesis of N1/N3-histidine modified by 2-hydroxyethylthioethyl and identification in sulfur mustard-exposed plasma - Long Wen; Zhibin Shu; Li Pan; Bo Chen; Gang Qu; Shu Geng; Yuntao Yang; Yan Jiang; Shilei Liu (Communications Chemistry)
Abstract Sulfur mustard (HD) alkylates biomolecules such as proteins, generating specific biomarkers. This study employs steric hindrance, electronic effects, and solvent effects through an occupancy-removal strategy to synthesize regioisomers [N1-HETE]-His and [N3-HETE]-His, overcoming isomer separation challenges in conventional methods. Density functional theory (DFT) calculations revealed hexafluoroisopropanol (HFIP)’s critical role in directing HD’s regioselective alkylation: HFIP modulates steric and electronic environments to preferentially target N1 or N3 sites of histidine imidazole rings, with predictions validated experimentally. The method further enables selective detection of the isomers in HD-contaminated plasma via standard addition, advancing absolute quantification. This work not only establishes a precision synthesis platform for biomarkers but also elucidates HFIP’s unique role in imidazole regioselectivity, offering insights for medicinal chemistry and HD toxicology. These findings hold implications for HD exposure tracking, mechanism analysis, clinical diagnostics, and antidote development.